Pendampingan Program Dokter Cilik untuk Penguatan Keterampilan Hidup Sehat pada Peserta Didik SDN 1 Pohgading Timur - Ahmad Syiehamul Ishobah; Arif Rahman Hakim; Leni Juniarti; Helma Nadia; Nadia Arum Finasty; Fitri Sasmita (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service aims to improve students' knowledge, attitudes, and behaviors related to clean and healthy living practices. This activity was carried out through a qualitative descriptive approach with a participatory mentoring method. The target of the activity is elementary school students who are guided to play the role of child doctors, namely young health ambassadors who are tasked with promoting hygiene and a healthy lifestyle to their peers. The implementation of the program consists of several stages, namely initial coordination with the school, delivery of educational materials on Clean and Healthy Living Behavior (PHBS), practical demonstrations, and reflective discussions. The results of the activity showed that students actively participated and experienced increased awareness about personal and environmental hygiene. They are able to implement healthy habits, such as washing hands, bringing healthy lunches, and maintaining classroom cleanliness. Teachers and school staff are also actively involved in supporting the implementation of the program, thus enabling the sustainability of activities as part of health education in schools. Participatory mentoring has proven to be effective in strengthening students' healthy living skills and building a sense of responsibility and leadership in maintaining health. Thus, the pediatrician program can be concluded as a valuable model in building a school health culture through collaboration between educators, students, and the school community more broadly.